Prevalence of Parental Bereavement Among Female Sex Workers (FSW) in Kibra, Kenya. Issue 2 (17th February 2019) - Denckla, Christy A.; Ongeri, Linnet; Ouma, Linet; Singa, Benson; Maingi, Charity; Bosire, Rose; Otieno, Phelgona; Omolo, Danvers; Henderson, David C.; Chibnik, Lori B.; Koenen, Karestan C.; Manduku, Veronica
Abstract: Female sex workers (FSW) residing in Kibra, Kenya, experience elevated exposure to adverse events, yet the prevalence of parental bereavement is not well characterized. This cross-sectional pilot study on 301 FSWs residing in Kibra, Kenya, found that 67.7% of these women were parentally bereaved. Significantly fewer parentally bereaved women reported historical use of condoms and emergency contraception compared to nonbereaved women, and older age of paternal bereavement was significantly associated with current contraceptive use. Prevalence rates of bereavement among this cohort are well over the national Kenyan average, and further research on the specific impact of bereavement is warranted.